2021
DOI: 10.1186/s10020-021-00370-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation of the proliferation and apoptosis of Leydig cells in diabetes

Abstract: Background The number of patients with diabetes is increasing worldwide. Diabetic testicular damage can cause spermiogenesis disorders and sexual dysfunction. We thus explored the role of miRNAs in diabetic testicular damage, and revealed that they could serve as effective prevention and treatment therapeutic targets. Methods Streptozotocin (STZ) was used to generate a rat model of type 2 diabetes. Rat testicular tissues were used for miRNA and mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…As microRNAs (miRNAs) are small and highly conserved endogenous ncRNAs, most of them regulate posttranscriptional gene expression in mammals by targeting the mRNA 3′-untranslated region (3′-UTR) [ 13 ]. It has also been suggested that a single miRNA may target multiple mRNAs, which jointly regulate the exact molecular or cellular processes [ 31 , 32 ]. We hypothesized that the terminal gene of miR-369-3p that plays a functional role in disc degeneration might also pass through BMP2 in addition to CDH2.…”
Section: Discussionmentioning
confidence: 99%
“…As microRNAs (miRNAs) are small and highly conserved endogenous ncRNAs, most of them regulate posttranscriptional gene expression in mammals by targeting the mRNA 3′-untranslated region (3′-UTR) [ 13 ]. It has also been suggested that a single miRNA may target multiple mRNAs, which jointly regulate the exact molecular or cellular processes [ 31 , 32 ]. We hypothesized that the terminal gene of miR-369-3p that plays a functional role in disc degeneration might also pass through BMP2 in addition to CDH2.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, higher LH levels could suggest a subclinical primary hypogonadism due to initial testis impairment. Indeed, several studies demonstrated that both hyperglycemia and hyperinsulinemia could damage the blood–testis barrier, which can lead to Leydig cell apoptosis and decrease spermatogenesis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the miR-197-3p and miR-504-5p in our study showed downregulation, with a previous report demonstrating that the inhibition of miR-197-3p represses cell apoptosis ( Li et al, 2019 ). Additionally, the stimulation of miR-504 can enhance the apoptotic machinery ( Hu L. et al, 2021 ). Together, it implies that the downregulation of miR-197-3p and miR-504-5p induced by BRV infection would suppress cell apoptosis to improve viral replication.…”
Section: Discussionmentioning
confidence: 99%